PENGEMBANGAN BUKU CERITA BERSERI UNTUK SISWA KELAS V SDN 14 PONTIANAK SELATAN - Natasya, Dya; Salimi, Asmayani; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The lack of motivation and enthusiasm for learning in class V students at SD Negeri 14 Pontianak Selatan is one of the backgrounds for developing this series of storybooks as an effort to increase their learning motivation. This research aims to produce a series of storybooks "Mengapa Aku Harus Belajar?", determine the level of feasibility, and determine the response of teachers and students to the books produced. The method used is Research and Development (RD) with the ADDIE development model modified to the development stage. The sample in this study was 2 expert validators, 1 teacher, and 16 students. The data collection techniques used were interviews and questionnaires. The research results show that the story book series "Mengapa Aku Harus Belajar?" those produced and developed received the criteria of being very suitable for use with a percentage of material aspects of 97.91%, design aspects of 93.33%, and language aspects of 91.66%. The development of this book also received a very positive response from teachers with a percentage of 95%, and also received a positive response from students with a percentage of 79.51%. It was concluded that the storybook product series "Why Should I Study?" can be used as an effort to increase the learning motivation of class V students at SD Negeri 14 Pontianak Selatan.